An Inverse Method to Estimate Cowper‑Symonds Material Model Parameters from a Single Split Hopkinson Pressure Bar Test (2023)
This paper presents the estimation of the parameters of the Cowper-Symonds material model of a commercial copper alloy from a single Split Hopkinson Pressure Bar Test using an inverse method. Parameters were identified by minimizing the error between the transmitted strain signal predicted by a finite element model and those observed experimentally. The Taylor Test was used to validate the identified parameters by comparing the experimental final length of impacted specimens and the ones predicted by a finite element model using the identified parameters. Also, identified parameters were contrasted with those found by a traditional curve-fitting approach. It was found that finite element models using the identified parameters are better able to predict plastic deformation than those using parameters from traditional curve-fitting.